A LEO Satellite Handover Strategy Based on Graph and Multiobjective Multiagent Path Finding - Zhiyun Jiang; Wei Li; Xiangtong Wang; Binbin Liang (International Journal of Aerospace Engineering, 2023)
Low earth orbit (LEO) satellite network can provide services to users anywhere on the earth. However, the high-speed mobility of satellites leads to a dynamic environment, which brings challenges for handover and network performance optimization, especially in the scenario of multiuser using the networks meanwhile. In this paper, we exploit multiple directed graphs to model the handover process for multiuser. The nodes in a graph represent the satellites that the corresponding user may choose to access. The edges represent the possible handovers between adjacent timestamps. The path from the start node to the end node in each graph is the handover strategy of the corresponding user, and the path length is the reward that the user can get. Therefore, the handover strategy problem is transformed into a path planning problem. To minimize the average handover times, maximize the average received power, and minimize the average number of conflicts, we propose a novel handover strategy based on multiobjective multiagent path finding (MOMAPF). The simulated handover experiment on Starlink successfully derives the Pareto-optimal solution set, which corroborates the effectiveness of the proposed handover strategy. The results also show that the proposed strategy has better comprehensive performance than other strategies.